Isolation of Bacteriophages against Enterobacteria spp. Isolated from Poultry Waste - Shruti Bhosale; Neha Lanke; Nayan Kolhe; Manisha Shinde (The Bioscan, 2025)
The increasing occurrences of antibiotic-resistant bacterial infections in poultry poses a significant challenge to the poultry industry, necessitating alternative therapeutic approaches. This study explores the potential of bacteriophage therapy as a biocontrol measure against Enterobacteria spp infections in poultry. Enterobacterium is a major pathogen responsible for economic losses due to increased morbidity and mortality. In this study, two Enterobacter isolates were obtained from poultry waste samples, characterized using cultural, morphological, biochemical characters and confirmed by 16S rRNA sequencing. Four lytic bacteriophages were isolated from poultry waste samples and were studied to determine their lytic ability against host Enterobacter. The most potent lytic phage was selected, purified and enriched for further studies. The potent lytic ability of selected phage demonstrated that these phages specifically target and lyse their corresponding Enterobacteria spp hosts, suggesting their potential as a substitute to antibiotics for managing bacterial infections in poultry. This study highlights the viability of phage therapy as a sustainable and active approach to combating antibiotic-resistant Enterobacteria spp strains in poultry farming.